PROYEK REHABILITASI GEDUNG KANTOR DINAS PENDIDIKAN KABUPATEN SELUMA (REANALISIS GEDUNG) - gunawan, agustin (Inersia: Jurnal Teknik Sipil, 2022)
Control measures for concrete structures need to be carried out so that deviations can be reduced as much as possible so that damage or decrease in the quality of the planned concrete can be avoided. The Seluma Education Office building was tested for the feasibility of its column and sloof structure based on the request of the BPK RI. Concrete samples were taken from as many as 7 specimens of concrete cylinders using the core drill method (3 samples in the column and 4 samples in the sloof). From the results of the compression test and analysis of the test results, it is known that the average compressive strength of concrete achieved in the field is below the target concrete compressive strength value in the design. Hence, it is necessary to reanalyze the structure using the existing material properties. Structural modeling is carried out to determine the internal forces that occur in the structural elements, as well as the behavior of the structure due to the working load. The results of the structural modeling are used as the basis for designing the cross-sectional dimensions of the structural elements along with the required reinforcement. The results of building reanalysis show that the condition of several columns (KS) and Sloof (SL1) are declared unsafe, so the potential for structural failure in this building appears in extreme conditions that must be taken into account, including earthquakes and full loading conditions. Options for engineering methods that can be done include: changing the function of the building so that the live load that must be borne is reduced and or strengthening structures that are indicated to be unsafe.